Pengaruh Kompetensi Perangkat Desa, Kepemimpinan Kepala Desa, Partisipasi Masyarakat, dan Kejelasan Sasaran Anggaran terhadap Akuntabilitas Pengelolaan Dana Desa - Febrianti, Resty; Amalia, Dewi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Accountability is a critical policy within government management systems, essential for fostering public trust in the activities and programs developed and executed by the government for the public good. This study examines the impact of village officials' competencies, the leadership of village heads, community participation, and the clarity of budget targets on the accountability of village fund management in Sewon District, Bantul Regency. This study employed a survey method utilizing questionnaires. The sample comprised 37 respondents, chosen through purposive sampling. Multiple linear regression analysis was used to test the hypotheses. The findings indicate that the competence of village officials positively influences the accountability of village fund management. In contrast, the leadership of village heads, community participation, and clarity of budget targets do not positively impact the accountability of village fund management in Sewon District, Bantul Regency   .